A new species of the genus Hoplias (Characiformes, Erythrinidae), a tararira from the lower Paraná River in Misiones, Argentina - Azpelicueta, Maria de Las M. (2015)
We describe Hoplias mbigua, a new species of the genus from the lower Paraná, in Misiones, with tooth-bearing plates on dorsal surface of basihyal and basibranchials and medial margins of contralateral dentaries converging towards the mandibular symphysis in ventral view, characters that permit to include the species in the H. malabaricus group. The presence of five brown bands transversely placed on lower jaw distinguishes the new species from its congeners, excluding H. microlepis (vs. lower jaw straight or with small black or brown dots uniformly distributed). The number of circunpeduncular scales in H. mbigua is 20 whereas H. teres and H. malabaricus have 18 circunpeduncular scales and H. microlepis 22-24 and 12-16 gill rakers on first epibranchial (vs. about 9). Hoplias mbigua has convex dorsal profile between head and dorsal fin whereas H. teres has straight dorsal profile. Hoplias mbigua has a large supraopercle, with its anterior margin contacting the in- fraorbitals 5 and 6 whereas H. cf. malabaricus has a short supraopercle, with an anterior margin scarcely extended before anterior opercular margin. Hoplias mbigua has a large tooth-plate on basihyal and basibranchials instead of two lines of tooth-plates at sides of bones in H. cf. malabaricus.